Youth libraries: overcoming an inherited cliché - Lozano-Díaz, Roser (Anuario ThinkEPI, 2015)
With the failure of school libraries in Spain and public libraries that are more targeted to adult patrons, it seems that the library authorities have forgotten about services to adolescents. The specific needs of young people aged between 14 and 18 years are not being met. It is proposed that the successful information commons (or resource centers for learning and research, as they are known in Spain) of the universities be made available to non-college youth through cooperation agreements with public administration.
Keywords: Adolescents; Teenagers; Youth; Library services; Public libraries; Information commons; Cooperation.